Triple-rule-out dual-source CT angiography of patients with acute chest pain: dose reduction potential of 100 kV scanning - Kriššák, Radko; Henzler, Thomas; Reichert, Miriam; Grüttner, Joachim; Süselbeck, Tim; Schönberg, Stefan; Fink, Christian (European journal of radiology, 2012)
Purpose: To investigate the dose reduction potential of low kV triple-rule-out dual-source CT angiography (TRO-CTA) in non-obese (BMI ≤ 25 kg/m2) patients with acute chest pain. Materials and methods: Sixty consecutive patients were randomly assigned to two different retrospectively ECG-gated TRO-CTA protocols in this prospective trial: Thirty patients were examined with a 120-kV standard protocol (320 reference mAs with automatic tube current modulation, automatically adapted pitch and ECG-pulsing) and served as the control group (group 1), an otherwise identical 100 kV protocol was used in the other thirty patients (group 2) for a radiation dose reduction. Subjective image quality was assessed on a 5 point scale (1: excellent, 5: non-diagnostic) by two blinded observers. Quantitative image analysis assessed vascular attenuation, signal-to-noise ratio (SNR) and contrast-to-noise ratio (CNR) in different vascular segments. The effective dose was calculated from the dose length product (DLP) using a conversion coefficient of 0.017 mSv mGy−1 cm−1. Results: There was no significant difference of age, BMI, heart rate, pitch or scan length between both patient groups. Subjective image quality was rated similar in both groups (group 1: 1.2 ± 0.4, group 2: average score = 1.3 ± 0.5). Vessel attenuation was significantly higher in group 2 than in group 1 (ascending aorta: 456 ± 83 HU vs. 370 ± 78 HU, p < 0.001; pulmonary artery: 468 ± 118 HU vs. 411 ± 91 HU, p = 0.03; left coronary artery: 437 ± 110 HU vs. 348 ± 89 HU, p < 0.001), however, there was no significant difference in SNR (13.2 ± 7.6 vs. 14.5 ± 7.5, p = 0.49) or CNR (13.8 ± 6.6 vs. 15.9 ± 7.7, p = 0.25). The effective radiation dose of the 100 kV protocol was significantly lower (9.6 ± 3.2 mSv vs. 18.1 ± 9.4 mSv, p < 0.0001). Conclusion: TRO-CTA with 100 kV is feasible in non-obese patients and results in diagnostic image quality and significantly reduced radiation dose.
Available online 15 December 2010
Gesehen am 25.06.2018